UI/UX Design of Ruang Kajian Application Using Design Thinking Method - Jannah Arum Kemangi, Anisya Khanza Afiatul; Efrat Najaf, Abdul Rezha; Permatasari, Reisa (International Journal of Engineering, Science and Information Technology, 2025)
Islamic Studies, or Dirasah Islamiyah, explores various aspects of Islamic teachings. In Indonesia, where Islam is the majority religion, many organizations actively promote da’wah through study sessions, sholawat, and dhikr. However, the Better Youth Foundation lacks a dedicated platform to support its Better Youth Academy programs, which involve structured Islamic studies. This highlights the need for an efficient and accessible platform to facilitate learning and positive activities. This study develops the Ruang Kajian mobile application using the Design Thinking method, which consists of five stages: Empathize, Define, Ideate, Prototype, and Testing. The approach ensures a user-centered design, focusing on usability testing based on ISO 9241-11 standards and evaluating Effectiveness, Efficiency, and Satisfaction. The proposed design allows users to register and participate in Better Youth Academy sessions efficiently while accessing various structured study materials. Testing results from five users showed Effectiveness at 90%, Efficiency at 92.33%, and Satisfaction at 83.40%, indicating the design’s high usability. This research demonstrates that Design Thinking can produce user-friendly and efficient UI/UX designs that meet user needs and preferences. It offers practical guidance for developers in creating intuitive interfaces while enhancing the user experience when accessing Ruang Kajian.